2020
DOI: 10.1111/gfs.12495
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum silage quality as determined by chemical–nutritional factors

Abstract: Forage availability depends on seasonality, and this may cause problems for farmers maintaining regular livestock productivity throughout the year. Therefore, forage conservation as silage has become an important and popular method of feed storing because it can minimize the loss of nutrients after harvest during storage (Fulgueira, Amigot, Gaggiotti, Romero, & Basílico, 2007). Sorghum [Sorghum bicolor (L.) Moench] is a tropical plant that efficiently uses water and it is a good alternative to maize crops for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
4
0
2
Order By: Relevance
“…The average CP content obtained for the silages studied is consistent with values reported by other authors for S. bicolor and S. bicolor × S. sudanense types (Herrmann et al, 2011; Mahmood et al, 2013; Rodrigues et al, 2020). This parameter was significantly affected by the sorghum type for the Marquardt variants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The average CP content obtained for the silages studied is consistent with values reported by other authors for S. bicolor and S. bicolor × S. sudanense types (Herrmann et al, 2011; Mahmood et al, 2013; Rodrigues et al, 2020). This parameter was significantly affected by the sorghum type for the Marquardt variants.…”
Section: Discussionsupporting
confidence: 90%
“…In relation to these findings, S. bicolor types at HD2 presented the best conditions as a pre‐ensiled material for both sites and years, with WSC contents reaching 11%DM in some cases. Rodrigues et al (2020) reported a similar WSC average (10.7%DM) for S. bicolor types. McDonald et al (1991) reported that the optimum nitrate content is in the range of 0.6%–1.0%TS, and the results for fresh materials were in all cases below this range.…”
Section: Discussionmentioning
confidence: 68%
“…Regarding the potential of improvement of the in vitro dry matter digestibility, the key importance of the cell wall digestibility, that exhibits a larger genetic variance than IVDMD, and that depends of the composition of the cell wall (as also reported by Rodrigues et al, (2020)) but also of the spatial distribution of the tissues and of the cell wall components at the internode level was reported. These results are consistent with the ones reported in maize (El Hage et al, 2018; Legland et al, 2017) and advocate for the development of higher throughput histological methods to facilitate breeding efforts.…”
Section: Discussionmentioning
confidence: 67%
“…An increase in LA of silage indicates an increase in SCHO concentrations in sorghum mixed with PP. Rodrigues et al (2020) estimated that each percentage unit of SCHO in sorghum DM raised 0.37 units of LA in silage DM until a plateau of 8.42% of LA was obtained with 12.54% of SCHO, which coincides with pH stabilization at ~3.62. With a mixed silage, the average pH (3.60) was close to the maximum pH reduction proposed by Rodrigues et al (2020).…”
Section: Resultsmentioning
confidence: 98%